Analyzing the Impact of Interest Among Sharia Economics Students at UIN Sayyid Ali Rahmatullah Tulungagung on Sharia Stock Investment - Eylen Jisan Fitriangga; Deris Lazuardi; Rokhmat Subagiyo; Ummu Sholihah (FEBI IAIN Langsa, 2024)
Abstract Sharia investment is a form of economic activity that invests various types of money in accordance with sharia law in the hope of obtaining profits in the future. This research uses quantitative methods, and the type of research uses associative research. The data collection method uses purposive sampling where the number of respondents is 101. These respondents are Sharia Economics students of UIN Sayyid Ali Rahmatullah Tulungagung class of 2022-2023. Primary data is also used in this study, where the type of data is through questionnaires or questionnaires, surveys, interviews and so on. This study aims to determine how much influence the interest of Sharia Economics students of UIN Sayyid Ali Rahmatullah Tulungagung class of 2022-2023 in terms of financial literacy, advances in financial technology, capital, and financial behavior. The results of this study indicate that all variables affect or have a positive and significant influence on the interest of Islamic Economics students of UIN Satu batch of 2022-2023 in investing in Islamic stocks. Because the data has a sig. value, which is less than 5% and has an estimated t value of more than 1.984 except for the financial technology progress variable which has no influence or the variable does not have a positive and significant influence on the student's interest in investing in Islamic stocks. Abstrak Investasi syariah merupakan suatu bentuk kegiatan ekonomi yang menginvestasikan berbagai jenis uang sesuai dengan hukum syariah dengan harapan memperoleh keuntungan di kemudian hari. Penelitian ini memakai metode kuantitatif, dan jenis penelitiannya memakai jenis penelitian asosiatif. Metode pengumpulan data menggunakan purposive sampling yang dimana jumlah respondennya yaitu sebanyak 101. Responden tersebut adalah mahasiswa Ekonomi Syariah UIN Sayyid Ali Rahmatullah Tulungagung angkatan Tahun 2022-2023. Data primer juga digunakan dalam penelitian ini, yang dimana jenis data melalui angket atau kuesioner, survei, wawancara dan lain sebagainya. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh minat mahasiswa Ekonomi Syariah UIN Satu angkatan Tahun 2022-2023 ditinjau dari literasi keuangan, kemajuan teknologi keuangan, modal, dan perilaku keuangan. Hasil dari penelitian ini, bahwasannya semua variabel berpengaruh atau memiliki pengaruh positif dan signifikan terhadap minat mahasiswa Ekonomi Syariah UIN Satu angkatan Tahun 2022-2023 dalam melakukan investasi pada saham syariah. Sebab data tersebut memiliki nilai sig., yang kurang dari 5% dan memiliki nilai t estimasi lebih dari 1.984 kecuali variabel kemajuan teknologi keuangan yang tidak memiliki pengaruh atau variabel tersebut tidak memiliki pengaruh positif dan signifikan terhadap minat mahasiswa tersebut dalam berinvestasi pada saham syariah.